If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3 + -2m + 3(6 + 3m) = 7m + 3(5m + -2) 5 + 3 + -2m + (6 * 3 + 3m * 3) = 7m + 3(5m + -2) 5 + 3 + -2m + (18 + 9m) = 7m + 3(5m + -2) Reorder the terms: 5 + 3 + 18 + -2m + 9m = 7m + 3(5m + -2) Combine like terms: 5 + 3 = 8 8 + 18 + -2m + 9m = 7m + 3(5m + -2) Combine like terms: 8 + 18 = 26 26 + -2m + 9m = 7m + 3(5m + -2) Combine like terms: -2m + 9m = 7m 26 + 7m = 7m + 3(5m + -2) Reorder the terms: 26 + 7m = 7m + 3(-2 + 5m) 26 + 7m = 7m + (-2 * 3 + 5m * 3) 26 + 7m = 7m + (-6 + 15m) Reorder the terms: 26 + 7m = -6 + 7m + 15m Combine like terms: 7m + 15m = 22m 26 + 7m = -6 + 22m Solving 26 + 7m = -6 + 22m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-22m' to each side of the equation. 26 + 7m + -22m = -6 + 22m + -22m Combine like terms: 7m + -22m = -15m 26 + -15m = -6 + 22m + -22m Combine like terms: 22m + -22m = 0 26 + -15m = -6 + 0 26 + -15m = -6 Add '-26' to each side of the equation. 26 + -26 + -15m = -6 + -26 Combine like terms: 26 + -26 = 0 0 + -15m = -6 + -26 -15m = -6 + -26 Combine like terms: -6 + -26 = -32 -15m = -32 Divide each side by '-15'. m = 2.133333333 Simplifying m = 2.133333333
| x+x+5=39 | | -7+5=-11x+17 | | 6x^2+11=49 | | 17x=100 | | -10x+-30=-8x | | 6x+4y+7z-4x+5z-8y= | | 150=2x^3+x^2+x+10 | | H=15t | | B=1.0 | | y-.666666667=5 | | 4(v-9)=-6v+34 | | 2x+7*-1=5 | | -31x-4x=-5-5+25x | | -10x=-8x-8 | | 28x^3+48x^7= | | (x-1)/2/5/4 | | 4n-6+4n=2 | | 9x^4-24x^3-26x^2+56x-15=0 | | 4x^2-11=26 | | f(x)=9x^4-24x^3-26x^2+56x-15 | | 49v-90=-6v+34 | | -5-8=5x+9x-21x | | 192=3X | | -8x^2=-64 | | (1-4x)(1-3x)=6x(2x-1) | | 6,5/9=x/40 | | (5y+4w-3w-5)= | | N+4N=7N+22 | | 3.6b^3=42.5 | | 6x^2+9=4x^2+17 | | (5cd^-3/10d^5)^-1 | | (14x-28)/2x*8/7 |